PERANAN AKUNTANSI PERTANGGUNGJAWABAN DALAM KINERJA MANAJER PUSAT PERTANGGUNGJAWABAN - Andriana, Denny; Balqis, Kartika (Program Studi Akuntansi FPEB UPI, 2015)
This study was conducted with the aim to know the role of accounting responsibility in the performance of central managers accountability at PT. PINDAD (Persero). The research method used is descriptive method of analysis with survey approach, so that information collected from respondents using questionnaire. Sampling in this research using probability sampling technique. The variables tested are accountability (X) and performance of central responsibility manager (Y). Data analysis technique of this research using statistical analysis of simple correlation analysis Spearman Rank and to find out how big the role of variable X to variable Y is used coefficient of determination. Based on the calculation of correlation analysis with the help of SPSS 20.0 for Windows Software on 36 questionnaires at PT. PINDAD (Persero) resulted that there is a strong relationship between accounting accountability with the performance of central managers accountability that is equal to 0.831 with determination of 69.06%. This shows that accounting accountability has an effect of 69.06% in the performance of central managers accountability and the balance of 30.94% influenced by other factors not examined in this study.